Amp-CKlebsiella-Induced Chorioamnionitis and Associated Abnormalities in Cardiotocography: A Case Report with a Narrative Review - Sufia Athar; Anvar P. Vellamgot; Lolwa Mohammed Alansari (Case Reports in Infectious Diseases)
Introduction. Infections caused by multidrug-resistant organisms are on the rise in obstetric patients. Chorioamnionitis is associated with adverse pregnancy outcomes. If caused by multidrug-resistant organisms, chorioamnionitis is associated with high maternal and fetal morbidity. Due to the paucity of the literature and the challenges associated with their diagnosis, the diagnosis is usually delayed. This often leads to delays in management, and hence, adverse maternal and neonatal outcomes are noted. Important Clinical Findings. The patient presented with prelabour rupture of membranes for three days. She developed chorioamnionitis in labour, which was refractory to broad spectrum antibiotics. Persistent tachycardia with variable decelerations followed by prolonged fetal deceleration was observed in cardiotocography. Delivery of baby was done by cesarean section in the view of pathological findings in cardiotocography. The primary diagnoses, interventions, and outcomes. Based on the placental culture results, Amp-C Klebsiella-induced chorioamnionitis was diagnosed. Ertapenem was commenced after the sensitivity results. Good feto-maternal outcomes were observed. The neonate was admitted to the neonatal intensive care unit and discharged home in stable condition. Conclusions. Cases of multidrug-resistant organisms-induced chorioamnionitis are rarely reported, though they are associated with maternal morbidity and poor neonatal outcome. In cases of chorioamnionitis, caution should be taken in cases that are refractory to broad-spectrum antibiotics, and multidrug-resistant organisms should be suspected and managed to improve pregnancy outcome.